Dynamic Performance Improvement of Grid Interfaced Solar Photovoltaic System using Feed-forward Compensation - Kumar, Ajay; Gupta, Nitin; Gupta, Vikas (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: Solar Photovoltaic (PV) power generating system at the distribution end is emerged as the best solutions to meet the peak power demand during the day time. However, the highly intermittent nature of solar PV system demands a robust control, which is capable of serving a constant load demand even during solar intermittency. Objective: This paper presents a three-phase single-stage grid interfaced solar PV system, which includes PV array, perturb and observe based Maximum Power Point Tracking (MPPT) and Synchronous Reference Frame (SRF) based inverter control. Methods: The proposed three-phase voltage source inverter is controlled to match the DC bus voltage drained from the MPPT controller with sensed DC-link voltage amplitude in order to extract maximum power. The sudden change in irradiance and temperature causes oscillations in the DClink voltage amplitude, which further influences the dynamics of the system. Therefore, Feed- Forward Compensation (FFC) based control method is proposed to overcome the aforementioned limitations. Results: The current FFC method improves the speed of reference current estimation and the response of injected currents into the grid. As a consequence, rise time and settling time of the DClink voltage are reduced considerably. The stability of the voltage control loop is also increased by employing FFC based control method. Conclusion: The FFC-SRF based control presented in this paper offers several features including active power injection at the Unity Power Factor (UPF), power quality conditioning and reactive power compensation for local loads. Extensive MATLAB simulation results are presented for different conditions to validate the robustness of the controller under changing environmental conditions.
Keywords: SRF controller